INTERNALIZATION OF ISLAMIC SPIRITUAL CHARACTER EDUCATION VALUES IN THE EMPLOYEES AT PT. BUYA BAROKAH KUDUS - Ahmad Najih; Agus Nurhadi; Abdul Ghofur (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
In the current era of economic development, there is a form of capital rarely discussed in economics world, namely; spiritual capital. This spiritual capital is believed to have a positive influence on people's economy. The purpose of this study is to obtain an in-depth description of the implementation of the concept of Islamic spiritual capital at PT. Buya Barokah Kudus. The approach used is ethnography. This study will describe the work culture, behavior, beliefs and language of communication used by the management of PT. Buya Barokah Kudus in running the AMDK business. The results show that the importance of Islamic spiritual capital is reflected through the discipline of prayer, discipline of time and discipline of rules. Upholding the ethos of working hard, working smart and working consistently and sincerely. This work ethic involves the body, mind and heart. Islamic leadership is basically a belief that prioritizes the attributes of STAFF (Siddiq, Tabligh, Amanah, Fathonah). Motivation in working is directed to worship, seek the pleasure of Allah and become alms in the hereafter so that the goal of working is not only for the world. This makes employees have an Islamic commitment, namely having the confidence to be loyal to the organization and istiqomah (commitment) in working